Linguistic and Sociolinguistic Dimensions of Code-Switching in Television Talk Shows with Reference to Translation: MBC Channel as a Case Study - مسلم, قسام زياد جابر (An-Najah National University, 2021)
The linguistic phenomenon of code-switching between two or more languages is growing and spreading in the Arab World, especially Arabic-English switching. This thesis attempts to discover and investigate the ins and outs of code-switching in a place notably preeminent regarding code-switching, which is TV talk shows, through incorporating qualitative and quantitative methods using observation of the speakers’ talk and interviews with the shows’ guests and hosts. The assigned shows will be watched, and a corpus of English words, phrases and sentences are transcribed for analysis. In terms of a sociolinguistic perspective, the analysis of the collected data includes studying social variables that influence code-switching in the MBC shows, such as gender, age, and level of education. By then, some of the reasons behind those speakers choosing to switch to English will have been revealed. And for further discussion about switching reasons, interviews are conducted. Another section is dedicated to analyzing data that show morphological, syntactic and lexical observations. It describes and explains through instances from the shows how the integration of two different language systems ends. Finally, the thesis addresses the translation of code-switching as problematic. It attempts to provide solutions and advice for translating code-switching in shows. The paper finally concludes that code-switching is socially and linguistically a thriving phenomenon in shows and generally in the different fields of life. In addition, it proves that choosing a translation strategy for code switches actually depends on the genre of the ST.
الأبعاد اللغوية واللغوية الاجتماعية للتناوب اللغوي في البرامج الحوارية التلفزيونية وعلاقتها بالترجمة: قناة أم بي سي نموذجا